Intravenous Paracetamol Dosing Guidelines for Pain Management in (pre)term Neonates Using the Paediatric Study Decision Tree - Mian, P.; Knibbe, C. A.J.; Calvier, E. A.M.; Tibboel, D.; Allegaert, K. (Current Pharmaceutical Design, 2017)
Background: Intravenous paracetamol (acetaminophen) has not been licensed for analgesia in preterm neonates or infants < 2 years, respectively, in Europe and the United States. A variety of dosing regimens is therefore used off-label. Because evidence supports the use of the same target mean steady state paracetamol concentration (Cssmean, 9-11 mg/L) for pain relief in neonates compared to older children and adults, dosing regimens based on this Cssmean were evaluated in a two-step approach. Methods: First, a systematic search was performed to provide pharmacokinetic (PK)-based dosing guidelines for pain in neonates (with subsequent searches on safety in these papers). Second, concentration-time profiles based on these dosing guidelines were generated to provide a dosing advice for paracetamol to treat neonatal pain. Results: Of 2334 potentially relevant articles, 9 studies were included. For typical term neonates, dosages specified in packaging (labels) resulted in Cssmean below target (7.65 mg/L), while dosages from investigator-initiated studies resulted in either a Cssmean above (15.31), or around the target (11.78 and 10.21) for (pre)term neonates >32 weeks. Only one study suggested a dosing resulting in a tailored concentration (8.7) in preterm neonates <32 weeks. Conclusion: A loading dose 20 mg/kg, followed by 10 mg/kg/6h is recommended for 32-44 weeks' neonates, which is supported by short-term safety. For neonates < 32 weeks, a loading dose of 12 mg/kg and a maintenance dose of 6mg/kg/6h seems to lead to the target Cssmean, though additional clinical studies are needed to support its safety.
Keywords: paediatric study decision tree